Ibadah Mengolah Sampah di Desa Grobog Wetan Kecamatan Pangkah Kabupaten Tegal - Zaki Mubarok; Mohammad Koidin (LP2M of Institute for Research and Community Services - UIN Walisongo, 2020)
Having religion actually makes religious doctrine as an energy in solving the problems of humanity, one of them is the waste problem. The religious doctrine of the perfection of faith obtained by maintaining cleanliness must be realized by cooperating with multiple disciplines or other entities as an effort to create a clean and healthy society. The paradox of the society which is being busy with religious rituals, but neglecting the cleanliness of the environment continues until today, including in Grobog Wetan Village, Pangkah District, Tegal Regency. Initially this dedications was planned with the Almaghfiroh Foundation. However, in its development also with the Village Government, Youths, Fatayat, RT, RW and Nature Lovers Students.This dedication in dealing with the problem of garbage aims to bring up a paradigm of dealing with waste problems as a worshipping ritual, getting reward as in other rituals. It also makes waste as something which is close and can be treated as something economical. By using the society intervention method, the result of this service is a process in which the society developing a pattern of sorting and processing organic and inorganic waste. Organic waste is transformed into magot caterpillar food and inorganic waste is still in the process of being transformed into tradable goods. In addition, the fundamental achievement of this research-based dedication is the emergence of a new understanding for the society not to